Interpreting geology from geophysics in poly-deformed and mineralised terranes; the Otago Schist and the Hyde-Macraes Shear Zone. Issue 4 (2nd October 2019) - Blundell, Casey C.; Armit, Robin; Ailleres, Laurent; Micklethwaite, Steven; Martin, Adam; Betts, Peter
ABSTRACT: Ore deposits are formed by a variety of processes, and mineralised host rocks possess unusual petrophysical properties in contrast to un-mineralised country rock. Mineralised systems can therefore be identified directly in geophysical data via anomalous geophysical responses. In this paper, we review the interpretation of geology from aeromagnetic and electromagnetic data relative to orogenic gold systems. As a case study, we examine the Hyde-Macraes Shear Zone in eastern Otago, New Zealand, which hosts a world-class orogenic gold system within hydrothermally altered and graphitic schist. A subtle low-resistivity anomaly in electromagnetic data correlates well with the location of the mineralised shear zone, which is otherwise indistinct in aeromagnetic data. We interpret other candidates for mineralised structures to be present in similar low-resistivity features in the south of the study area. We interpret magnetite-bearing mafic bodies, and magnetite- and pyrrhotite-rich schists to be the source of regionally extensive, isoclinally folded anomalies which are prominent features in the magnetic and electrical data and allude to the complex accretion and deformation history of the Otago Schist. Future work encompassing detailed field analyses of low-resistivity anomalies in the south of the map may reveal suitable targets for exploration.